PRINCIPALSHIP OF EDUCATIONAL ORGANIZATIONS AND LEADERSHIP - RUIZ, PEDRO ADALID (IJRDO - Journal of Social Science and Humanities Research, 2018)
Leadership is a key factor in any community. One of the principal players in leadership, in educational organizations is principals. Principals take leadership roles in schools as such they are very important for the success of the school. However with the changing dynamics of the educational system all over the world, their job becomes more complex. This articles accesses and reiterate the position of principals, brings out facts about leaders and leadership, and then further specify leadership in educational setting. This article further elaborates on the conceptualization of leadership and also the challenges faced by leaders.